MEASURING PERCEPTIONS AND THE DRIVERS OF MEMBERSHIP COMMITMENT OF COCOA FARMERS’ COOPERATIVE SOCIETIES IN ATWIMA MPONUA DISTRICT, GHANA - Justice Frimpong-Manso; Enoch Kwame Tham-Agyekum; David Boansi; Fred Ankuyi; Evans Antwi; John-Eudes Andivi Bakang; Frederick Osei Tawiah; Fred Nimoh (Socio-Economics/Agribusiness Department, 2023)
Limited studies exist on the commitment of members to cooperative societies. Therefore, the study sought to measure perceptions of membership and the drivers of membership commitment of cocoa farmers' cooperative societies in the Atwima Mponua District of Ashanti Region, Ghana. Data was collected from a sample of 400 cocoa farmers through a multi-stage sampling technique. Descriptive statistics (mean and standard deviation) and inferential statistics (binary logit regression) were used in analyzing the data. Results show that cocoa farmers agree that they benefit from the cooperative and they appreciate the management, marketing and business, internal dynamics and public interest of their cooperatives. The study also discovered that farm age, access to extension service, farming experience, farmer status, cooperative benefits and internal dynamics are critical to obtaining commitment in cooperative societies. The study shows the need for the Ghana Cocoa Board to improve farmers’ access to extension services so as to improve their commitment in cooperative societies. Cooperative organizations are encouraged to consider the perceptions of the cocoa farmers and their socio-economic characteristics in order to elicit the desired commitment.